Effect of Construction Waste as a Fine Aggregate on Properties of Concrete. - Sempala, Ronald (Kabale University, 2023)
Construction and demolition (C&D) waste makes up a sizeable fraction of the world's overall production of solid waste, and the majority of it is dumped in landfills. Additionally, using routine construction materials like cement, fine and coarse aggregates results in significantly expensive construction costs. Therefore, the goal of the current study was to identify a different approach to dealing with the problem of these materials. As a result, it was discovered that using construction waste as a partial or complete replacement for fine or coarse aggregates could be a solution, and research by concrete engineers has amply demonstrated the possibility of properly treating and reusing such wastes in new concrete mixes, especially for lower-level applications. Construction debris, such as brick, block, and leftover mortar, was converted into aggregates by being manually or mechanically crushed in a jaw or impact crusher. A significant amount of waste (size smaller than 4.75 mm) was produced as by-product during this process. Construction waste was collected from three separate places and subjected to tests to determine its particle size distribution, fineness modulus, unit weight, specific gravity, and absorption capacity. As a result, the study covers the production of recycled aggregate concrete (RAC) from construction debris as well as its application in concrete construction. The report provides an overview of the engineering features of recycled aggregates as well as a synopsis of how recycled aggregates affect the characteristics of both fresh and hardened concrete. In order to continue all development efforts with the least possible harm to the environment and to obtain all the infrastructure needed to provide services and convenience in an affordable and environmentally friendly manner, research in this sector and successful outcomes are very essential. This research, however, shows that construction waste aggregates that are obtained from specific sites makes good quality concrete with sufficient strength characteristics. The influence of recycled fine aggregates on the compressive strength, density, modulus of elasticity, and workability of concrete is presented in this report. Recycled aggregate blend when used in concrete was in close proximity to normal concrete in terms of density and compressive strength. The slump value of recycled aggregate concrete was low and that can be improved by using saturated surface dry (SSD) coarse aggregate. The modulus of elasticity was also found to be decreasing from that obtained from natural aggregate concrete. Therefore, the study encompassed concrete properties in 3 different classes of M20, M25, and M30 using natural sand plus construction waste material as fine aggregates in new concrete.